Removal of Heavy Metals Fe3+, Cu2+, Zn2+, Pb2+, Cr3+ and Cd2+ from Aqueous Solutions by Using Eichhornia Crassipes - Shama,S.A. (2010)
The adsorption capacity of Eichhornia Crassipes towards metal ions such as Fe3+, Cu2+, Zn2+, Pb2+, Cr3+ and Cd2+, was studied. The adsorption capacity was investigated by batch experiments. The results showed that the removal percentages increased as the weight of sorbent increased, except for Fe3+ and Zn2+. The effect of contact time was also studied and the results showed that the removal percentages increased as the contact time increased for Cr3+, Zn2+ and Pb2+, but for Fe3+, Cu2+ and Cd2+ the removal decreased. The effect of pH of the solution was also studied and the removal percentages increased as pH increased. Also the effect of the initial concentration of metal ions was studied at four different concentrations (5, 10, 30, 50 mg/L); in case of metal ions (Cu2+, Zn2+ and Cd2+) the removal percentages increased by increasing initial concentration. But, for the other metal ions it decreased by increasing initial concentration over 30 mg/L. The order of increasing removal percentages of metal ions at pH=4.86, initial concentration of metal ions 30 mg/L, and after four hours of shaking was: Cu2+< Cr3+ <Cd2+< Zn2+ <Pb2+ <Fe3+.